Runaway replication of plasmid R1 is not caused by loss of replication inhibitor activity of gene cop. - Molin, S (1980)
The replication control functions of a mutant of plasmid R1 that replicates without control at temperatures above 35 degrees C have been analyzed. Although the mutations have not been mapped precisely, the data indicate that the gene (cop) previously identified on the wild-type plasmid (S. Molin and K. Nordström, J. Bacteriol. 141:111-120, 1980) as being responsible for expressing a trans-acting replication inhibitor, as well as for incompatibility of plasmid R1, is not affected in this mutant. Thus, the conditional lack of replication control observed in this plasmid mutant presumably is not caused by the loss of inhibitor activity of the cop gene.